Analisis Efektivitas Konten Edukasi Kesehatan Digital terhadap Peningkatan Pengetahuan dan Sikap Preventif Masyarakat Usia Produktif - Andi Makasau; Mira Permana Putri; Sudi Prayogi (Journal of Medical and Health Science, 2025)
The development of digital technology has driven changes in approaches to public health promotion and education. Digital health education content is increasingly used as a means of delivering flexible, accessible health information that is tailored to the characteristics of productive-age populations. This study aims to analyze the effectiveness of digital health education content in improving knowledge and preventive attitudes among productive-age populations. The study used a quantitative approach with a quasi-experimental design using a pretest–posttest method without a control group. The subjects were productive-age populations with access to digital devices and the internet. The intervention was carried out through the provision of visually and informative digital health education content. Data were collected using a structured questionnaire to measure respondents' levels of knowledge and preventive attitudes before and after the intervention. Data analysis was conducted descriptively and inferentially to assess changes that occurred after the education provision. The results showed a significant increase in respondents' levels of knowledge after the intervention, accompanied by a change in preventive attitudes towards more positive ones. These findings indicate that digital health education content is effective in increasing understanding and shaping preventive attitudes among productive-age populations. This study emphasizes the strategic role of digital health education as an adaptive and relevant alternative for health promotion in the digital era. The results are expected to form the basis for developing more effective and sustainable digital-based health education programs.